2007
DOI: 10.1080/00016480600818112
|View full text |Cite
|
Sign up to set email alerts
|

Habitual sniffing and postoperative configuration of the posterior meatal wall reconstructed with soft tissue

Abstract: The postoperative configuration of the posterior meatal wall showed severe retraction in 7 of 8 patients with habitual sniffing, but only 22 of 47 without habitual sniffing. Habitual sniffing was significantly associated with postoperative severe retraction (Fisher's exact test, p<0.05).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Kawase et al [16] reported that the cessation of habitual sniffing is one of the primary and most important ways to prevent postoperative retraction of the tympanic membrane. In the present study, we tried to encourage patients to cease sniffing and suggested that this effect would help prevent postoperative retraction of the tympanic membrane.…”
Section: Discussionmentioning
confidence: 98%
“…Kawase et al [16] reported that the cessation of habitual sniffing is one of the primary and most important ways to prevent postoperative retraction of the tympanic membrane. In the present study, we tried to encourage patients to cease sniffing and suggested that this effect would help prevent postoperative retraction of the tympanic membrane.…”
Section: Discussionmentioning
confidence: 98%
“…Habitual sniffing has been claimed to be a significant contributing factor to the development of postoperative retraction of the reconstructed posterior meatal wall and tympanic membrane [2]. Kawase et al [22] reported severe retraction of the posterior meatal wall was found in seven of eight patients with habitual sniffing, but was significantly less (22 of 47) in ears without habitual sniffing. Yamamoto-Fukuda et al [23] indicated that a tympanostomy tube was found to be effective in preventing the development of postoperative retraction of the reconstructed soft posterior meatal wall and tympanic membrane among cases with habitual sniffing.…”
Section: Discussionmentioning
confidence: 99%
“…Repetitive production of high negative middle ear pressure caused by habitual sniffing could be another cause of the retraction 17. In such cases, high negative middle ear pressure and subsequent retraction of the soft posterior meatal wall should happen frequently, with little regard to the condition of the mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…It seemed that such sniffing induces a high negative pressure in the middle ear and may sometimes cause cholesteatoma or its recurrence after surgery 13–16. In patients with acquired cholesteatoma who underwent the SWR method, Kawase and colleagues17 indicated a significantly frequent association of severe postoperative retraction of the soft wall with negative pressure caused by habitual sniffing, and concluded that habitual sniffing was one of the important causal factors for retraction‐type recurrent cholesteatoma.…”
Section: Introductionmentioning
confidence: 99%